Redistributing Central Bank Incomes and Expenses Across the Eurosystem: the Eurosystem’s Monetary Income - Cesaratto, Sergio; Febrero, Eladio; Pantelopoulos, George (Open economies review, 2025)
National Central Banks (NCBs) of the Eurosystem pool interest incomes and expenses related to monetary policy and the working of the payment system to form the Eurosystem’s so-called “monetary income”. This is then redistributed – i.e. allocated – among NCBs according to respective capital keys (the participation shares of each NCB to the ECB’s capital) to result in a final “net monetary income allocated” for each NCB. Such a process has relevance in the context of current debates such as those concerning the high fiscal costs of an ample reserve regime as a result of the abundant reserves banks hold in the deposit facility of their respective NCBs, as well as other puzzling issues like the supposed costs of TARGET2 imbalances. However, the process by which the monetary incomes of NCBs are pooled and subsequently allocated is still a rather little-known subject to many academics and the wider public. To this end, the predominant purpose of this paper is to disseminate how the initial incomes and expenses of Eurosystem NCBs are pooled and allocated subject to certain rules to result in a final net monetary income position for each NCB. This process in many cases reallocates the costs of an ample reserve regime among NCBs and neutralises the costs associated to TARGET2 imbalances for NCBs.